2011
DOI: 10.33899/mmed.2011.34639
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and lipid profile among depot- medroxyprogesterone acetate injections users

Abstract: Objective:To study the effect of depot-medroxyprogesterone acetate (DMPA) injections on Creactive protein (CRP) and lipid profile and to find the predictors (body weight, body mass index (BMI), blood pressure (BP) and lipid profile) that significantly predict the risk of cardiovascular disease (CVD) among DMPA injections users. Method: A prospective cohort study was performed during the period from March 2009 to March 2010 included thirty apparently healthy married women, their age ranged between 20-35 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…Moreover, a recent study conducted to assess dietary intake and weight gain among adolescents on Depo-Provera, demonstrated that mean BMI increased significantly from 23.7 ± 5.3 at the baseline to 25.3 ± 5.7 after 12 months of using of Depo-Provera with increased mean percentage body fat significantly [14]. While other studies indicated Depo-Provera users pose increased body weight in comparison to their controls, however, changes were not statistically significant [6]. This could be due to the difference in race/ethnicity, which is associated with weight gain, where black women had a greater mean weight gain compared to white, Bushmen, oriental and Papuan with continued Depo-Provera use [9, 16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent study conducted to assess dietary intake and weight gain among adolescents on Depo-Provera, demonstrated that mean BMI increased significantly from 23.7 ± 5.3 at the baseline to 25.3 ± 5.7 after 12 months of using of Depo-Provera with increased mean percentage body fat significantly [14]. While other studies indicated Depo-Provera users pose increased body weight in comparison to their controls, however, changes were not statistically significant [6]. This could be due to the difference in race/ethnicity, which is associated with weight gain, where black women had a greater mean weight gain compared to white, Bushmen, oriental and Papuan with continued Depo-Provera use [9, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Depo-Provera is among a highly effective, convenient non-daily injectable hormonal contraceptive option with a very low failure rate that has been available worldwide for many years. The recommended dose of this contraceptive is 150 mg, administered by deep intramuscular (IM) injection at the interval of 3 months using strict aseptic technique in the gluteal or deltoid muscle [6, 7]. Side effects of this contraceptive method include: changes in menstrual patterns, loss of bone mineral density and risk of weight gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In theory, progesterone also stimulates the appetite control center in the hypothalamus by activating neuropeptide Y, resulting an increase in appetite which will affect the percentage of body fat, body mass index, and waist circumference of its users. 6,7 The research conducted by Youzbaki (2011) in Iraq regarding lipid profiles in 30 subjects using DMPA showed higher mean triglyceride levels in DMPA acceptors, namely (170.26±58.74) mg/dl than non DMPA acceptors, namely (147.74±74.76) mg/dl with p = 0.226 (p>0.05), which means that there were no statistically significant differences in the two groups. 8 Research conducted by Gisele (2017) in Brazil showed that the mean BMI of DMPA acceptor group was higher (24.88±3.43) than the IUD acceptor group, namely (24.56±2.84) with p value = 0.007 which means that there was a difference in BMI between DMPA and IUD acceptor.…”
Section: Introductionmentioning
confidence: 98%
“…6,7 The research conducted by Youzbaki (2011) in Iraq regarding lipid profiles in 30 subjects using DMPA showed higher mean triglyceride levels in DMPA acceptors, namely (170.26±58.74) mg/dl than non DMPA acceptors, namely (147.74±74.76) mg/dl with p = 0.226 (p>0.05), which means that there were no statistically significant differences in the two groups. 8 Research conducted by Gisele (2017) in Brazil showed that the mean BMI of DMPA acceptor group was higher (24.88±3.43) than the IUD acceptor group, namely (24.56±2.84) with p value = 0.007 which means that there was a difference in BMI between DMPA and IUD acceptor. 9 Research conducted by Bonny (2009) stated that most DMPA acceptor fat percentage was 20-30% with body mass index ranged from 18.5 to 24.9, showing p value <0.05, which means that there was no difference in DMPA users with fat percentage and body mass index.…”
Section: Introductionmentioning
confidence: 98%